Pelatihan Praktikum Kimia Sederhana di SMAN 16 Padang - Imelda Imelda; Refinel Refinel; Refilda Refilda; Yefrida Yefrida; Hermansyah Aziz; Yulizar Yusuf; Suryati Suryati; Zulkarnain Chaidir; Sumaryati Syukur; Rahmiana Zein; Novesar Jamarun; Safni Safni; Zilfa Zilfa; Yetria Rilda; Norman Ferdinal; Tommi Hermansyah; Fivi Mona Bareno (Warta Pengabdian Andalas, 2023)
Chemistry is one of the subjects taught in State Senior High Schools (SMAN), especially in Natural Sciences (IPA). The problem with chemistry subjects is that it is difficult to practice in the laboratory because laboratory facilities such as space, equipment and chemicals are expensive. As a result, chemical laboratory practices were only sometimes carried out. Several lecturers and students from the Department of Chemistry, FMIPA Unand Kimia Unand, carried out service activities at SMAN 16 Padang through laboratory practice using materials and equipment that were cheap and readily available in the surrounding environment. This community service aims to train teachers and students to carry out chemistry practicums using simple materials and equipment available around them. The training was given to chemistry subject teachers and students in the science laboratory at SMAN 16 on 17 and 21 November 2022. The material was practised in oxidation and reduction (redox) and electrolysis reactions. The activity went smoothly; the students enthusiastically carried out the practicum. Through the results of this simple chemistry practicum, students can design and carry out chemical experiments using simple tools and materials, conduct direct observations of chemical processes, practice scientific thinking, attitude and work skills and analyze and solve various scientific processes using scientific methods. SMAN 16 hopes that this activity will continue with different topics.